Thermal supplies of Tarys Springs (South-East Tuva): profiles of micro-chemical structure - Oydup, Choyganmaa K.; Kurbatskaya, Svetlana S.; Dongak, Roman Sh. (The New Research of Tuva, 2014)
Article presents the detailed geological specification of Tarys thermal springs area (Republic of Tuva, Russian Federation). Initial full micro-chemical structure of subsoil waters and Arzhaanets creek is presented.